COMPARATIVE LITERATURE AND TRANSLATION STUDIES: THEORY AND PRACTICE - Mahmudova Munisaxon Foziljon qizi,; Ruzmetova Diana Komilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This paper examines the close relationship between Comparative Literature and Translation Studies, focusing on how texts move and gain meaning across languages and cultures. It outlines key concepts such as intertextuality, equivalence, and cultural transfer,  showing  how  translation  serves  both  as  a  comparative  tool  and  an  act  of interpretation. The study emphasizes the role of these disciplines in enhancing cross-cultural  communication,  supporting  world  literature,  and  promoting  global  literary understanding.